Pengaruh Price Discount terhadap Loyalitas Konsumen pada Pengguna Online Marketplace - Salsabila Wulandari Aryatiningrum; Athiyyah Isna Insyirah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
College students are the generation that lives side by side with current communication technology. To conduct activities such as shopping, many college students also use the online marketplace for reasons that are more practical and do not take up time and effort. This is the reason why college students are the target for consumers who are often targeted for marketing products to sell well. How to get loyal customers is often done by giving price discounts for their product. The purpose of this study is to conduct an analysis of customer loyalty in the online marketplace who affected by price discounts in their product. This research is quantitative research. The sample used consisted of 60 people who decisions in 2018 and 2019 psychology students in Surabaya State University. This sample is taken by purposive sampling method. Data are collected by using a questionnaire with a Likert scale as a measurement and will be analyzed with a simple linear regression technique that helps by the SPSS program. The results of this study are, there is a significant positive influence on price discounts and consumer loyalty in online marketplace users.